Prospective evaluation of pregnant women suspected of acute toxoplasmosis attended in a reference antenatal clinic in a university teaching hospital in Southern Brazil - Evangelista, Fernanda Ferreira (2019)
Orientador: Profª. Drª. Ana Lúcia Falavigna Guilherme.